2017
DOI: 10.1002/jat.3563
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles increase connexin43‐mediated gap junctional intercellular communication in HaCaT cells through activation of reactive oxygen species and mitogen‐activated protein kinase signal pathway

Abstract: Silver nanoparticles (AgNPs) are widely used in health and consumer products that routinely contact skin. However, the biological effects and possible mechanisms of AgNPs on skin remain unclear. Gap junctional intercellular communication (GJIC) plays a critical role in multicellular organisms to maintain tissue homeostasis. The aim of this study is to examine if non-coated AgNPs affect GJIC in human keratinocytes (HaCaT cells), and to identify the possible molecular mechanisms responsible for the effects. GJIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…These results suggested that Cx26, rather than Cx43, might be involved in the GJIC inhibition of BPA in HaCaT cells. We also found that the GJIC inhibition of BPA could be partly rescued by ICI Previous studies have shown that HaCaT cells can express phosphorylated Cx43, but the phosphorylated forms were not evident in western blots (Qin et al, 2017;Tacheau, Laboureau, Mauviel, & Verrecchia, 2008). Similar results were also obtained in this study.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggested that Cx26, rather than Cx43, might be involved in the GJIC inhibition of BPA in HaCaT cells. We also found that the GJIC inhibition of BPA could be partly rescued by ICI Previous studies have shown that HaCaT cells can express phosphorylated Cx43, but the phosphorylated forms were not evident in western blots (Qin et al, 2017;Tacheau, Laboureau, Mauviel, & Verrecchia, 2008). Similar results were also obtained in this study.…”
Section: Figuresupporting
confidence: 91%
“…Previous studies have shown that HaCaT cells can express phosphorylated Cx43, but the phosphorylated forms were not evident in western blots (Qin et al, ; Tacheau, Laboureau, Mauviel, & Verrecchia, ). Similar results were also obtained in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Further, the potential molecular mechanisms in EPA-induced Cx43 expression were determined in B16F10 cells. Recently, a different MAPK kinase expression might involve the particles-induced regulation of Cx43 expression 18. In this study, the phosphorylation of JNK and p38 were increased after EPA treatment, but the phosphorylation of ERK was not observed (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…The same phenomenon has also been observed in Fig 5(A) shows that the anti-oxidative activity of AP may help in protecting the skin from UVA-induced ROS over-expression, which acts as a free radical scavenger. A previous reports clearly showed that the main reasons that influence AgNP-induced Cx43 upregulation include: changes in reactive oxygen content and activation of extracellular signal-regulated kinase and c-Jun N-terminal kinas [ 60 ]. Interestingly, we found that the AP protection mechanism is different from silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%